62.1k views
0 votes
What is the solution to the following system of equations?

4x + 2y = 6
x − y = 3

User CrazyCrow
by
7.3k points

2 Answers

3 votes

Answer:

x = 2, y = -1

--------------------------------

Hope this Helps! :)

User John Starr Dewar
by
7.1k points
7 votes

Answer:

x = 2, y = -1

Explanation:

4x + 2y = 6 ------- eq 1

x − y = 3 -------- eq 2

Using elimation method:

eq 2 x 2

2 (x − y)= 2(3 )

2x - 2y = 6 ---- eq 3

eq 1 + eq 3

4x + 2y + 2x - 2y = 6 + 6

6x = 12

x = 2 (sub this back into eq 2)

x − y = 3

2 − y = 3

-y = 3 - 2

-y = 1

y = -1

User Bjorsig
by
7.6k points